2012
DOI: 10.1021/am301751s
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiradical SiO2 Nanoparticles Covalently Functionalized with Gallic Acid

Abstract: Gallic acid (GA) and its derivatives are natural polyphenolic substances widely used as antioxidants in nutrients, medicine and polymers. Here, nanoantioxidant materials are engineered by covalently grafting GA on SiO(2) nanoparticles (NPs). A proof-of-concept is provided herein, using four types of well-characterized SiO(2) NPs of specific surface area (SSA) 96-352 m(2)/g. All such hybrid SiO(2)-GA NPs had the same surface density of GA molecules (~1 GA per nm(2)). The radical-scavenging capacity (RSC) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
178
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(195 citation statements)
references
References 52 publications
6
178
0
11
Order By: Relevance
“…In the case of HNT-Cur, the n value is about 2 for both ROO • and oDPPH • radicals suggesting a more complex mechanism. A stoichiometry decrease of the radical trapping was previously observed for phenols linked to nanoparticles [62,68] in agreement with the self-decay of the radical of the antioxidant (A • in Eq. (6)), which is not involved in the trapping of a second radical because of the formation of A-A dimers [67].…”
Section: Dpph • Bleaching Experimentssupporting
confidence: 86%
“…In the case of HNT-Cur, the n value is about 2 for both ROO • and oDPPH • radicals suggesting a more complex mechanism. A stoichiometry decrease of the radical trapping was previously observed for phenols linked to nanoparticles [62,68] in agreement with the self-decay of the radical of the antioxidant (A • in Eq. (6)), which is not involved in the trapping of a second radical because of the formation of A-A dimers [67].…”
Section: Dpph • Bleaching Experimentssupporting
confidence: 86%
“…For instance, a covalent link between gallic acid (a food-grade antioxidant) and SiO 2 nanoparticles (SiO 2 NPs) was proposed for reducing its leaching and volatility, and this material showed radical trapping activity toward the 1,1-diphenyl-2-picrylhydrazyl (DPPH ) radical. 6 Some of us recently demonstrated that carbon-coated cobalt nanomagnets decorated by a-tocopherol units are able to effectively counteract the autoxidation of organic substrates, and can be efficiently controlled by an external magnet. 7 Nanomaterials can also serve as carriers for controlled release of antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large variety of currently known antioxidants, 2 several challenges still exist in specific applications such as in food technology, 21 pharmaceutical and cosmetics technology, or for biomedical applications, namely: (a) the potential toxicity of several antioxidants; 22 (b) antioxidant leaching or migration to unwanted compartments, 23 which is a major challenge in food preservation 24 and food packaging; 6 With the aim of further improving the usefulness and versatility of HNT-based antioxidants, we have devised the synthesis of novel HNT nanomaterials, in which different phenolic antioxidants are, for the first time, both loaded in the inner lumen and grafted on the outer surface. Indeed, the combining of different antioxidant functions on the same nanostructured material would sum up the advantages outlined in points (a)-(d) and offer distinctive additional advantages, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research team of Yiannis Deligiannakis, a visiting professor at the Institute of Process Engineering at the Swiss Federal Institute of Technology in Zurich (ETHZ), has developed a nanoantioxidant with enhanced stability (Deligiannakis et al, 2012). This discovery is published in the journal ACS Applied Materials and Interfaces.…”
Section: Introductionmentioning
confidence: 99%